Construction of a Poly(anthraquinone Sulfide)/Carbon Nanotube Composite with Enhanced Li‐ion Storage Capacity. Issue 9 (4th May 2021) - Mao, Wutao; Ding, Yiming; Li, Maolong; Ma, Chao; Cao, Zhixiang; He, Chang; Bao, Keyan; Qian, Yitai
Abstract: Quinone compounds are among the most promising candidate organic materials for energy storage due to advantages such as their higher theoretical energy density. In the present paper, a one‐step condensation method is described for connecting anthraquinone units via thioether bonds to generate a poly(anthraquinone sulfide) (PAQS) material as a promising lithium energy‐storage system. Poly(anthraquinone sulfide)/carbon nanotube (PAQS/CNT) frameworks are then prepared via an in‐situ chemical solution method. The good electrochemical performance of the PAQS/CNT composite with 2 wt % carbon nanotubes is then demonstrated, with a significantly higher discharge specific capacity (187.2 mA h g −1 ) than that of a pure PAQS electrode (101.0 mA h g −1 ). Moreover, the specific capacity remains at 168.4 mA h g −1 after 200 cycles, with a retention rate of 90.0 %. It is confirmed that CNTs play a number of roles in the composite polymer material, such as stabilizing the material structure during battery charging and discharging, improving the electronic conductivity, and alleviating the dissolution of the components of the organic electrolyte. Abstract : A poly(anthraquinone sulfide)/carbon nanotube composite is synthesized by a one‐pot method. The polymer material forms a honeycomb structure with carbon nanotubes as the frame, which stabilizes the structure and improves the electronic conductivity.